Acquisition and Homeostasis of Iron in Higher Plants and Their Probable Role in Abiotic Stress Tolerance - Tripathi, Durgesh K.; Singh, Shweta; Gaur, Shweta; Singh, Swati; Yadav, Vaishali; Liu, Shiliang; Singh, Vijay P.; Sharma, Shivesh; Srivastava, Prateek; Prasad, Sheo M.; Dubey, Nawal K.; Chauhan, Devendra K.; et al. (Frontiers in Environmental Science, 2018)
Iron (Fe),a micronutrient,plays an important role in agriculture world wideand its smaller amount because a small amount is required for plant growth and development.All major functions in thea plant’s life from chlorophyllbiosynthesisto energy transfer are performed by Fe.Iron also acts as a major constituent of many plant proteins and enzymes. The Acacquisition of Fein plants occurs throughby two strategies i.e. stragegystrategy I and strategy II. Under various stress conditions, Nramp and the YSL gene families help in translocation of Fe,which further actsas amineral regulatory element and defends plants against stresses.Iron plays an irreplaceable role in alleviating stress imposed by salinity,drought, and heavy metal stress. This is because,as it activates plant enzymatic antioxidants like catalase (CAT),peroxidase, andone anisoform of superoxide dismutase (SOD) whichthat act as a scavengers of reactive oxygen species (ROS).In contrast, both its deficiency and excess amount can disturb the homeostasis of the a plant’s cell as a result of via decliningits declining the photosynthetic rate, respiration, and increased accumulation of Na+ and ClCal- ions which ultimately resulted intoculminate in an excessive formation of ROS. The short-range-order hydrated Fe oxides and organic functional groups show affinities for metal ions. Iron plaque biofilm matricesx could sequester a large amount of metals at the soil-root interface.Hence, it has attracted the attentions of plant physiologists and agricultural scientists for who are discovering more exciting and hidden applications of Fe and its potential in the development of bio-factories.This review looks into recent progress made in putting forward the role of Fe in plant growth, development, and acclimation under major abiotic stresses i.e.salinity, drought, and heavy metals.